2018
DOI: 10.1111/1742-6723.13153
|View full text |Cite
|
Sign up to set email alerts
|

Management of post‐partum haemorrhage in the Timor Leste National Ambulance Service

Abstract: This research has shown that paramedics are not consistently using available clinical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 5 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…In Fiji, trauma management has been improved through enhanced surveillance and team‐based care; in Papua New Guinea, action research has helped optimise asthma treatment; and in the Solomon Islands, inconsistent triage (a challenge in many Pacific Island countries) has been addressed by a simple, locally developed triage system . Despite experiencing significant disasters, Indonesia and Myanmar have only recently developed specialty training in emergency medicine (EM) and have identified that the crucial pre‐hospital EC needs can be assisted by simple rural systems and basic protocols …”
Section: Ec and The Indo‐pacificmentioning
confidence: 99%
See 1 more Smart Citation
“…In Fiji, trauma management has been improved through enhanced surveillance and team‐based care; in Papua New Guinea, action research has helped optimise asthma treatment; and in the Solomon Islands, inconsistent triage (a challenge in many Pacific Island countries) has been addressed by a simple, locally developed triage system . Despite experiencing significant disasters, Indonesia and Myanmar have only recently developed specialty training in emergency medicine (EM) and have identified that the crucial pre‐hospital EC needs can be assisted by simple rural systems and basic protocols …”
Section: Ec and The Indo‐pacificmentioning
confidence: 99%
“…24 Despite experiencing significant disasters, Indonesia and Myanmar have only recently developed specialty training in emergency medicine (EM) 25,26 and have identified that the crucial pre-hospital EC needs can be assisted by simple rural systems and basic protocols. 27,28 What has happened so far?…”
Section: Ec and The Indo-pacificmentioning
confidence: 99%
“… 7 26 184 LMIC EMS priorities are known to differ: some function exclusively or primarily for obstetric patients, 175 185–188 some focus on trauma, 189 190 while some cover trauma, obstetric and medical conditions in similar proportions. 32 33 Knowing and reporting this context should be part of incorporating EMS data meaningfully in future studies.…”
Section: Discussionmentioning
confidence: 99%
“… 25 29 Although many mechanisms can cause injury, patient management protocols standardise initial treatment priorities, regardless of aetiology. 30 31 Both are acute-onset, time-critical conditions, 5 with overlapping health system response requirements including timely facility transfer, 32 33 anaesthesia 34 and haemorrhage control. However, they differ in funder priority, 35 36 community and cultural understanding, 37 38 and the demographic characteristics of affected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of evidence-based, context appropriate clinical guidelines to improve EC exist for trauma care in Fiji [40] and acute asthma in PNG, [41] as well as a framework for developing and sharing locally adapted clinical EC guidelines. [42] The need for pre-hospital clinical practice guidelines is highlighted in Timor-Leste, [43] as one component of many essential Process priorities and standards required to build an effective prehospital system.…”
Section: Tablementioning
confidence: 99%